2007
DOI: 10.1161/strokeaha.107.487017
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of Statin Therapy and Clinical Outcome After Ischemic Stroke

Abstract: Background and Purpose-The majority of patients with previous ischemic stroke are expected to benefit significantly from long-term statin therapy. However, discontinuation of medication therapy frequently occurs in clinical practice. The aim of this study was to assess the impact of discontinued statin therapy on clinical outcome in patients discharged after an acute ischemic stroke. Methods-The study population included 631 consecutive stroke survivors (322 men and 309 women; meanϮSD age, 70.2Ϯ7.6 years) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 34 publications
6
113
0
2
Order By: Relevance
“…The current study found adverse effects in patients who did continue statins through the acute period but then were no longer on the therapy more than 3 months after onset. A single‐center study found increased mortality among patients stopping statins in the first year after stroke 6. Our study affirms the deleterious effect of stopping statins after the initial period following a stroke but does so in a population 30‐fold larger, demonstrates increased risk of recurrent stroke, and controls more rigorously for the healthy‐user effect.…”
Section: Discussionsupporting
confidence: 71%
“…The current study found adverse effects in patients who did continue statins through the acute period but then were no longer on the therapy more than 3 months after onset. A single‐center study found increased mortality among patients stopping statins in the first year after stroke 6. Our study affirms the deleterious effect of stopping statins after the initial period following a stroke but does so in a population 30‐fold larger, demonstrates increased risk of recurrent stroke, and controls more rigorously for the healthy‐user effect.…”
Section: Discussionsupporting
confidence: 71%
“…Exposure to statins in the acute phase of experimental stroke appears to promote angiogenesis and synaptogenesis,15 and additional pleiotropic statin effects such as vasodilatory and antithrombotic properties have been reported 16. These experimental observations are supported by clinical findings of improved outcomes with acute statin use in myocardial infarction,17, 18, 19 stroke,3, 4, 20, 21 and major vascular surgery 22, 23…”
Section: Discussionmentioning
confidence: 86%
“…These errors include discontinuation of prescribed medications; noncompliance, including failure to fill medications or failure to be adherent; and delays in filling medications. [5][6][7] In the geriatric population, the most frequently reported unwanted events after discharge were related to prescription medication regimens mainly due to patients getting incorrect drugs or dosages. 8 Literature to date shows that some pharmacist interventions before and after discharge decrease medication-related errors.…”
mentioning
confidence: 99%